Integration of cell of origin into the clinical CNS International Prognostic Index improves CNS relapse prediction in DLBCL - Klanova, Magdalena; Sehn, Laurie H; Bence-Bruckler, Isabelle; Cavallo, Federica; Jin, Jie; Martelli, Maurizio; Stewart, Douglas; Vitolo, Umberto; Zaja, Francesco; Zhang, Qingyuan; Mattiello, Federico; Sellam, Gila; et al. (Blood, 2019)
Central nervous system (CNS) relapse carries a poor prognosis in diffuse large B-cell lymphoma (DLBCL). Integrating biomarkers into the CNS-International Prognostic Index (CNS-IPI) risk model may improve identification of patients at high risk for developing secondary CNS disease. CNS relapse was analyzed in 1418 DLBCL patients treated with obinutuzumab or rituximab plus cyclophosphamide, doxorubicin, vincristine, prednisone chemotherapy in the phase 3 GOYA study. Cell of origin (COO) was assessed using gene-expression profiling. BCL2 and MYC protein expression was analyzed by immunohistochemistry. The impact of CNS-IPI, COO, and BCL2/MYC dual-expression status on CNS relapse was assessed using a multivariate Cox regression model (data available in n = 1418, n = 933, and n = 688, respectively). High CNS-IPI score (hazard ratio [HR], 4.0; 95% confidence interval [CI], 1.3-12.3; P = .02) and activated B-cell‒like (ABC) (HR, 5.2; 95% CI, 2.1-12.9; P = .0004) or unclassified COO subtypes (HR, 4.2; 95% CI, 1.5-11.7; P = .006) were independently associated with CNS relapse. BCL2/MYC dual-expression status did not impact CNS relapse risk. Three risk subgroups were identified based on the presence of high CNS-IPI score and/or ABC/unclassified COO (CNS-IPI-C model): low risk (no risk factors, n = 450 [48.2%]), intermediate risk (1 factor, n = 408 [43.7%]), and high risk (both factors, n = 75 [8.0%]). Two-year CNS relapse rates were 0.5%, 4.4%, and 15.2% in the respective risk subgroups. Combining high CNS-IPI and ABC/unclassified COO improved CNS relapse prediction and identified a patient subgroup at high risk for developing CNS relapse. The study was registered at www.clinicaltrials.gov as #NCT01287741.
Keywords: Young Adult; protoonkogenní proteiny c-myc; Central Nervous System Neoplasms; Male; mutace; lokální recidiva nádoru; Antineoplastic Combined Chemotherapy Protocols; mladý dospělý; následné studie; Adolescent; Lymphoma, Large B-Cell, Diffuse; nádory centrálního nervového systému; Adult; Aged; dospělí; mužské pohlaví; senioři; incidence; mladiství; Follow-Up Studies; Neoplasm Recurrence, Local; senioři nad 80 let; lidé; ženské pohlaví; difúzní velkobuněčný B-lymfom; Biomarkers, Tumor; Humans; protokoly protinádorové kombinované chemoterapie; Aged, 80 and over; Proto-Oncogene Proteins c-myc; prediktivní hodnota testů; protoonkogenní proteiny c-bcl-2; Proto-Oncogene Proteins c-bcl-2; Mutation; Female; lidé středního věku; Incidence; Predictive Value of Tests; nádorové biomarkery; Middle Aged